Assisted Dying in Canada: Ideology Masquerading as Medicine? - Kim, Scott (Canadian Journal of Bioethics / Revue canadienne de bioéthique, 2025)
The Canadian medical assistance in dying (MAID) law is commonly understood as a type of medically-based euthanasia and/or assisted suicide (EAS) law. I argue it is instead an autonomy-only EAS regime masquerading as such. The public guidance on the law’s broad eligibility criteria that direct current practice employs novel meanings to familiar terms used in healthcare. The result is that the law gives the impression that Canadian MAID is about something medical, but in reality operates as an autonomy-only model, i.e., “death on autonomous demand” clothed as medical treatment. The implications are significant. It allows bypassing the debates that an autonomy-only system (which is not inherently medical) would need to address, such as whether autonomy-only EAS comports with common morality, whether and how the health care system should be involved, how many resources the state should invest in promoting a death-on-request system, etc. The law also distorts the practice of medicine by using patients’ subjective preference (i.e., patients’ preference), rather than science and evidence, as determining medical standards and in defining terms such as ‘incurable.’ This masquerade has been reinforced by Canadian officials in their public statements. The result seems to be a Canadian public highly supportive of a law that they do not fully understand and indeed would likely disapprove of in its current form, if they did. The Canadian MAID law is a product of flawed democratic policymaking.